Analisis Kebutuhan Materi Audio berdasarkan Kurikulum Pembelajaran Bahasa Indonesia Kelas XII Australia - Meita Enjayani (Universitas Lampung, 2019)
Indonesian Languange for Foreign Speaker (BIPA) has shown good development ecery year. One country with high number of Indonesian Language learners is Australia. As a close neighbor of Indonesia, Australia has special attention to Indonesian language. Some schools in Australia even require students to learn Indonesian language. Based on the initial interview with one of the teacher, it reveals that Indonesian learning materials for class XII in form of audio is still needed. Therefore, researchers are interested in conducting needs analysis to get an overview of the learning material needed as a foundation to conduct research and development. This research is the initial stage of development research. This is need analysis process to gather relevant information on the research. Need analysis is done through interviews with teachers and document analysis of class XII Indonesian learning curriculum. The results of this study shows that there is a great need of developing authentic audio material which is related to the topics such as texts and genres, media and entertainment, globalization and the media, youth issues, social issues, and Australian / Indonesian relations. DOI: http://dx.doi.org/10.23960/aksara/v20i1.pp1-9